Dependent Revenues, Capital Risk and Credit Rationing - Johannes Reeder; Stefanie Trepl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
Much of the literature on financial markets has not dealt with dependency of project revenues. In a setup similar to the seminal SW model, we show that the type of equilibrium can crucially depend on the degree of project dependency. By making aggregate payoffs risky, households face capital risk. Therefore, risk aversion and households' consumption-savings decision become very important. Capital risk deters households from saving so that there might be a credit rationing equilibrium. Defining the social optimum, we find that project dependency might reduce the number of safe projects in equilibrium in a socially harmful way. Thus, project dependency can aggravate adverse selection. In three extensions, we will show how risk aversion, imperfect revenue dependency and a different modelling of dependency influence our results. Our analysis points out that project dependency is an important factor in the determination of credit market outcomes.
Keywords: 330